In Vitro and In Vivo Tumor Growth Inhibition by Glutathione Disulfide Liposomes. (9th March 2017) - Sadhu, Satya S; Wang, Shenggang; Dachineni, Rakesh; Averineni, Ranjith Kumar; Yang, Yang; Yin, Huihui; Bhat, G Jayarama; Guan, Xiangming
Glutathione disulfide (GSSG) is an endogenous peptide and the oxidized form of glutathione. The impacts of GSSG on cell function/dysfunction remain largely unexplored due to a lack of method to specifically increase intracellular GSSG. We recently developed GSSG liposomes that can specifically increase intracellular GSSG. The increase affected 3 of the 4 essential steps (cell detachment, migration, invasion, and adhesion) of cancer metastasis in vitro and, accordingly, produced a significant inhibition of cancer metastasis in vivo. In this investigation, the effect of GSSG liposomes on cancer growth was investigated with B16-F10 and NCI-H226 cells in vitro and with B16-F10 cells in C57BL/6 mice in vivo. Experiments were conducted to elucidate the effect on cell death through promotion of apoptosis and the effect on the cell cycle. The in vivo results with C57BL/6 mice implanted subcutaneously with B16-F10 cells showed that GSSG liposomes retarded tumor proliferation more effectively than that of dacarbazine, a chemotherapeutic drug for the treatment of melanoma. The GSSG liposomes by intravenous injection (GLS IV) and GSSG liposomes by intratumoral injection (GLS IT) showed a tumor proliferation retardation of 85% ± 5.7% and 90% ± 3.9%, respectively, compared with the phosphate-buffered saline (PBS) control group. The median survival rates for mice treated with PBS, blank liposomes, aqueous GSSG, dacarbazine, GLS IV, and GLS IT were 7, 7, 7.5, 7.75, 11.5, and 16.5 days, respectively. The effective antimetastatic and antigrowth activities warrant further investigation of the GSSG liposomes as a potentially effective therapeutic treatment for cancer.